MODERN STRATEGIES IN PROSE LITERATURE PEDAGOGY - Agbaje, J. O. (Sokoto Educational Review, 2020)
This paper discusses some of the modern strategies in Prose Literature pedagogy. It emphasizes that any useful method of teaching should be based on the modern theory of learning which places the child at the center of the teaching/learning activity; and that the teacher, in the choice of methods, should bear in mind several variables including: the nature of the learners, the objective of the teaching programme, the learning environment, etc.